2006
DOI: 10.1007/s11244-006-0077-7
|View full text |Cite
|
Sign up to set email alerts
|

A study of the electronic structure and reactivity of V/TiO2(110) with metastable impact electron spectroscopy (MIES) and ultraviolet photoelectron spectroscopy (UPS)

Abstract: The interaction of vanadium with TiO 2 (110) surface was studied with metastable impact electron spectroscopy (MIES) and ultraviolet photoelectron spectroscopy (UPS) under ultrahigh vacuum (UHV) conditions. A strong interaction between vanadium and TiO 2 is observed with the addition of the first vanadium layer. Adsorption and reaction of ethanol to ethylene were investigated with MIES, UPS and temperature programmed desorption (TPD) and found to be sensitive to the surface electronic structure. In particular … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 31 publications
2
17
0
Order By: Relevance
“…An adsorption of an electron donor species may reduce it, leading to the oxidation degree ?III. There are experimental investigations of the interface between firstrow transition metal atoms and TiO 2 (110) [19][20][21][22][23][24][25][26][27]. These studies indeed indicate the possibility of a charge transfer from the metal to the Ti cations in agreement with theoretical results [28,29].…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…An adsorption of an electron donor species may reduce it, leading to the oxidation degree ?III. There are experimental investigations of the interface between firstrow transition metal atoms and TiO 2 (110) [19][20][21][22][23][24][25][26][27]. These studies indeed indicate the possibility of a charge transfer from the metal to the Ti cations in agreement with theoretical results [28,29].…”
Section: Introductionsupporting
confidence: 70%
“…In the cases of Ni and Cu, the bridge site is the only stable position; optimization starting from h led to b. h site was proposed for the alkali metals [54,55]. The h site was also recently found as the preferred adsorption site in the cases of V and Fe [19,23]. For some atoms, the interaction energies are very close for both cases.…”
Section: Computational Detailsmentioning
confidence: 99%
“…Studies addressing V / r-TiO 2 (110) have revealed a strong interaction between V and the support both at sub-monolayer and full-monolayer (ML) coverages [22], [24], [31], [32]. It was found that V oxidizes and TiO 2 reduces upon V deposition [21], [23], [24], [30], [33], [35]. It should be noted that the highest V oxidation state in these studies is lower than +5.…”
Section: Introductionmentioning
confidence: 77%
“…It should be noted that the highest V oxidation state in these studies is lower than +5. Because of the importance of the V 5+ oxidation state, numerous studies have aimed at a characterization of the VO x / TiO 2 system under various oxidation conditions [20], [22]- [25], [33], [35]. Two oxidation methods have been applied most frequently, namely post-oxidation (V deposition in UHV and subsequent oxygen exposure) and reactive evaporation (V deposition in an oxygen background).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation